Kasih, Otoritas, dan Relevansi: Menerapkan Kepemimpinan Gereja Pentakosta dalam Pelayanan Generasi Z - Twin Yoshua R. Destyanto; Purim Marbun (Jurnal Apokalupsis, 2025)
The role-modeling crisis among young people motivates this study to explore how Pentecostal church leadership can effectively engage Generation Z (Gen Z), a demographic known for valuing authenticity, empathy, and relational depth. With Gen Z increasingly present in faith communities, especially among university students, the research investigates how Pentecostal leadership values align with their spiritual and emotional needs. Using a qualitative method, this study combines a literature review with in-depth interviews with six Gen Z members from a Pentecostal church in Yogyakarta. The findings reveal that Gen Z resonates deeply with Spirit-led, inclusive, adaptive, and relational leadership. Respondents emphasized the importance of empathetic leaders who are present in real life and exhibit integrity and humility. They appreciated leadership that empowers participation, respects their individuality, and communicates spiritual truths in relevant ways. The study concludes that effective Pentecostal leadership for Gen Z must move beyond traditional authority-based models to embrace relational ministry grounded in spiritual authenticity. Such an approach not only nurtures personal growth but also fosters lasting engagement and discipleship within the church